Anti-Idiotypic Antibody as a Booster Vaccine Against Respiratory Syncytial Virus - Shreya Mukhopadhyay; Ioannis Manolaridis; Christopher Warren; Aimin Tang; Gregory O’Donnell; Bin Luo; Ryan P. Staupe; Kalpit A. Vora; Zhifeng Chen (Vaccines)
Background/Objectives: The respiratory syncytial virus (RSV) is a major cause of lower respiratory tract infections in children and adults. With nearly everyone infected by the age of five, there is an opportunity to develop booster vaccines that enhance B-cell immunity, promoting potent and broadly neutralizing antibodies. One potential approach involves using anti-idiotypic antibodies (anti-IDs) to mimic specific antigenic sites and enhance preexisting immunity in an epitope-specific manner. RB1, a monoclonal antibody (mAb) that binds to site IV of the RSV fusion (RSV F) protein, is a potent and broadly neutralizing against RSV A and B viruses. It is the precursor for MK1654 (clesrovimab), which successfully completed a Phase III clinical trial. Methods: In this study, we isolated two anti-IDs, 1A6 and 1D4, targeting RB1 CDR regions, demonstrating that 1A6 competes fully with RSV F in binding to RB1. Results: We resolved the RB1-1A6 and RB1-1D4 Fab-Fab complex structures and proved that 1A6 mimics the RSV F site IV better than 1D4. In an immunogenicity study, mice primed with RSV F and boosted with 1A6 Fab showed a site IV-specific antibody response with a concurrent increase in RSV virus neutralization. Conclusions: These results suggest that anti-IDs could be potentially used as booster vaccines for specific epitopes.